Curcumin: A review of experimental studies and mechanisms related to periodontitis treatment. (26th June 2021) - Li, Yongli; Jiao, Junjie; Qi, Yuanzheng; Yu, Wanqi; Yang, Shihui; Zhang, Jingjie; Zhao, Jinghui
Abstract: Curcumin is the main active ingredient of turmeric, which has a wide range of pharmacological effects, including antitumor, antibacterial, anti‐inflammatory, anti‐oxidation, immune regulation, and so on. Periodontitis is a prevalent oral inflammatory disease caused by a variety of factors. In recent years, many studies have shown that curcumin has a potential role on the treatment of periodontitis. Curcumin has been used in research related to the treatment of periodontitis in the form of solution, chip, gel, and capsule. Combined with other periodontitis treatment methods, such as scaling and root planing (SRP) and photodynamic therapy (PDT), can enhance curcumin's efficacy in treating periodontitis. In addition to natural curcumin, chemically modified curcumin, such as 4‐phenylaminocarbonyl bis‐demethoxy curcumin (CMC 2.24) and 4‐methoxycarbonyl curcumin (CMC 2.5), have also been used in animal models of periodontitis. Here, this paper reviews the research progress of curcumin on the treatment of periodontitis and its related mechanisms.